Purchase Intention And Marketing Media: A Comparison Between Photos And Videos - Indasari Deu; Muhammad Baharudin Bakhtiar (Universitas Internasional Batam, 2024)
The selection of advertising media to be published to social media is a problem for business people to attract consumer attention. Along with the times, advertising media continues to develop and evolve into various advertising media. The purpose of this research is to find out the opinions of the public regarding the selection of advertising media in the form of photos or videos. The data source of this research was taken from 50 informants. This research uses the MDLC (Multimedia Development Life Cycle) method as a guideline for designing test materials. Descriptive qualitative method is used as an informant data collection by interview approach. The result of this research is an advertising media in the form of videos and photos and effective advertising media selection which shows that video advertising media is superior to be used as advertising media content selection.